Lower extremity thrombosis and myocarditis due to Human PVB19 infection - Ruba Zuhri Yafi; Ruba Haji Ali; Arwa El Rifai; Mariam Arabi; Jamal Jawad Hoballah (Elsevier, 2018)
This is a case report of a six years old boy who presented with seizure to the emergency department and was admitted for further evaluation. The following day he developed fever and ventricular tachycardia requiring cardioversion. Echocardiography revealed myocarditis and viral PCR was positive for PVB19. During his ICU stay he developed right lower extremity pallor and poikilothermia attributed to DVT and arterial thrombosis found on duplex. Despite IV heparin and therapeutic PTT levels, his lower extremity didn't improve and therefore he underwent thrombectomy. He was discharged six days postoperatively. At three month follow up, he was in good health. Keywords: Thrombosis, Myocarditis, PVB19